The Promoting Effect of Sports Dance Art Learning on College Students' Mental Health - Qing Li, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
The realm of sports dance exhibits elevated levels of aesthetic appeal and serves as an engaging avenue for fitness and entertainment. Combining elements of sports, dance, and music, sports dance offers a multifaceted platform conducive to the enhancement of both physical and mental well-being among college students, fostering an augmentation of their aesthetic acumen. In pursuit of this overarching significance, this study endeavours to investigate the catalysing influence of sports dance art education on the mental health of college students. This study focuses on a cohort of 50 university students enrolled in sports dance programs, utilizing a research methodology involving literature review, interviews, and statistical analysis to assess their mental health standard index scores. The collected data underwent rigorous statistical analysis via SPSS 16.0 software. A significance level (P-value) of greater than 0.05 suggests a lack of substantial disparity between the compared data groups, while P-values less than 0.05 indicate a notable distinction, and those below 0.01 denote a highly significant variance. Preceding the experiment, collegiate individuals were advised against holding overly optimistic views regarding the mental health standards associated with sports dance art education. Subsequent to the experiment's conclusion, a marked escalation in the mental health standards of college students was observed, with all pertinent health benchmarks and indicators demonstrating notable efficacy worthy of propagation. Following the experiment, discernible disparities were evident in the healthy personality traits and enriched emotional indicators among sports dance students, contrasting significantly with their pre-experiment states. Post-experiment, mental health indicators among sports dance college students follow this hierarchy: robust personality, heightened emotional depth, enhanced vitality, absence of psychological irregularities, and optimized cognitive faculties. We propose prerequisites to attract top talents and enhance existing educators' competencies. Instructors, acting as both executors and mentors, should inspire students with knowledge and charisma. Universities should diversify training and bolster pedagogical support for sports dance educators. Initiatives include expanded training opportunities and inter-institutional communication. In Yunnan Province, urgent short-term training and advanced education are needed to address the shortage of sports dance instructors and coaches. A long-term strategy is crucial to refine technical skills and performance.